Training on Classroom Action Research Proposal Making to Improve Skills for Social Studies Teacher Deliberation in Banjarbaru City - Ilhami, M. Ridha; Abbas, Ersis Warmansyah; Subiyakto, Bambang; Mutiani, Mutiani; Sari, Raihanah; Julia, Siti (Universitas Lambung Mangkurat, 2024)
The skills of junior high school social studies teachers in Banjarbaru City must be improved. Therefore, the Lambung Mangkurat University service team collaborated with MGMP IPS through a partnership program. The aim is to improve their ability to develop classroom action research (PTK) in that place. The purpose of this training is to improve teachers' ability to design PTK proposals in accordance with the needs of learning improvement. The training participants totaled 28 teachers, and the service methods used included lectures, interactive discussions, and PTK proposal clinic training. As a result of the training, junior high school social studies teachers who are members of MGMP IPS Banjarbaru City made several PTK proposals. In summary, teachers who attended the training were able to make a class action research proposal.